Challenges of using dielectric elastomer actuators to tune liquid lens - Keong, Gih-Keong (2014)
Recently, dielectric elastomer actuators (DEAs) have been adopted to tune liquid membrane lens, just like ciliary muscles do to the lens in human eye. However, it faces some challenges, such as high stress, membrane puncture, high driving voltage requirement, and limited focus distance (not more than 707cm), that limit its practical use. The design problem gets more complex as the liquid lens shares the same elastomeric membrane as the DEA. To address these challenges, we separate DEA from the lens membrane. Instead, a liquid-immersed DEA, which is safe from terminal failure, is used as a diaphragm pump to inflate or deflate the liquid lens by hydraulic pressure. This opens up the possibility that the DEA can be thinned down and stacked up to reduce the driving voltage, independent of the lens membrane thickness. Preliminary study showed that our 8-mm-diameter tunable lens can focus objects in the range of 15cm to 50cm with a small driving voltage of 1.8kV. Further miniaturization of DEA could achieve a driving voltage less than 1kV.